Impacts of gas flaring on soil physicochemical and microbial properties: A case study on kailashtila gas field - Kanij Fatema Aktar; Rony Basak; Sabrin Ara; Asif Mahmud (Heliyon, 2024)
Gas flaring, a common practice in many countries, has been associated with environmental and health concerns. A recent study in Bangladesh's largest gas field, Kailashtilla, assessed the influence of gas flaring on soil quality in the surrounding areas. Physical, chemical, and microbiological characteristics were assessed on soil samples collected from three union zones. Considerable influences have been found on soil quality, with several physical and chemical characteristics failing to meet the standards for healthy plant growth. Heavy metal contamination in the earth's soil was identified, specifically cadmium and lead, having a risk index indicating a moderate risk to the ecosystem in the future. Gas flaring also impacted the amount of bacteria in the soil, with the highest number being found farthest from the flaring zone. The soil was only marginally contaminated and potential health risks found. AAS and digestion methods were used to estimate the content of heavy metal contamination in the soil. To depict the geographically distributed abundance of heavy metals in the study area, the Kriging spatial interpolation procedure was utilized, and PCA and CA were used to assess the condition of soil. Findings indicate that particular gas flaring may have a deleterious influence on soil bacteria, which could have further consequences for the ecosystem. The study is likely to contribute to our understanding of the current state of soil's surrounding gas fields and serve as a platform for future research in this area emphasizing the necessity for sustainable energy methods and the importance of limiting environmental repercussions.